2014
DOI: 10.1126/scitranslmed.3009135
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-supported peritoneal dialysis for detoxification of drugs and endogenous metabolites

Abstract: Peritoneal dialysis confers therapeutic advantages in patients with renal insufficiency and has proven beneficial in other indications, such as removal of excess metabolites or overdosed drugs. However, it is used in only about 10% of the dialyzed population worldwide, partly owing to the lower clearance rate compared with hemodialysis. We have developed a dialysis medium based on liposomes with a transmembrane pH gradient (basic or acidic aqueous core) that could improve the efficacy of peritoneal dialysis, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 45 publications
0
79
1
2
Order By: Relevance
“…The liposomal formulation was more potent than the commercially available ILEs, with a recovery time more than 30% faster. Intraperitoneal injection of the liposomes allowed efficient sequestration of several drugs (propranolol, amitriptyline, haloperidol, phenobarbital, and verapamil) in the peritoneal cavity prior to removal; in the case of verapamil, peritoneal dialysis with liposomes resulted in a dramatic shortening of recovery time compared with standard peritoneal dialysis (20).…”
Section: System Specificity Xenobiotic Pros (+) and Cons (-) Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The liposomal formulation was more potent than the commercially available ILEs, with a recovery time more than 30% faster. Intraperitoneal injection of the liposomes allowed efficient sequestration of several drugs (propranolol, amitriptyline, haloperidol, phenobarbital, and verapamil) in the peritoneal cavity prior to removal; in the case of verapamil, peritoneal dialysis with liposomes resulted in a dramatic shortening of recovery time compared with standard peritoneal dialysis (20).…”
Section: System Specificity Xenobiotic Pros (+) and Cons (-) Statusmentioning
confidence: 99%
“…This response could be problematic in weakened, intoxicated patients, especially at the relatively high doses that are often injected in rescue protocols. One possible solution could be the administration of the antidotal particles intraperitoneally (20), to minimize systemic exposure to the drug scavengers. Another approach, although more invasive, could consist of purifying the blood extracorporally by passing it through a mesh containing the immobilized scavenging nanoparticles (64).…”
Section: Nano-antidote Strategies and Perspectivesmentioning
confidence: 99%
“…Their results showed clearance of ammonia approaching that of hemodialysis. They also successfully removed verapamil and were able to concentrate amitriptyline, propranolol, haloperidol and phenobarbital in the rat peritoneal cavity [65].…”
Section: Peritoneal Dialysismentioning
confidence: 98%
“…The ability of liposomes to encapsulate a wide variety of bioactive agents has led to substantial interest in utilizing liposomes as nanocarriers for the detection and treatment of a variety of diseases (15). Recently, Froster et al (17) developed a dialysis medium based on liposomes with a transmembrane pH gradient (basic or acidic aqueous core) and showed that liposome-supported peritoneal dialysis was able to improve the extraction of endogenous ammonia and ionizable drugs in rat models. For example, Wratten et al (16) reported that adding liposomes containing a-tocopherol (vitamin E) and ascorbic acid (vitamin C) to the dialysate reduced oxidant stress in the in vitro experiments.…”
mentioning
confidence: 99%